2014
DOI: 10.1245/s10434-014-4214-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Recurrence Patterns After Anatomical or Non-anatomical Resection for Hepatocellular Carcinoma

Abstract: The incidence and patterns of HCC recurrence were similar between the anatomical and nonanatomical resection. Recurrence by local dissemination may be considered to be negligible in both surgical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 31 publications
3
33
2
Order By: Relevance
“…Several reports have demonstrated the effectiveness of anatomical resection for HCC in terms of postoperative recurrence and survival [23, 25–28]. In contrast, other reports have demonstrated no obvious superiority of anatomical resection compared with non-anatomical resection [24, 29, 30]. To date, the clinical benefit of anatomical resection even for early HCC remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have demonstrated the effectiveness of anatomical resection for HCC in terms of postoperative recurrence and survival [23, 25–28]. In contrast, other reports have demonstrated no obvious superiority of anatomical resection compared with non-anatomical resection [24, 29, 30]. To date, the clinical benefit of anatomical resection even for early HCC remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…It is a higher incidence area of micrometastasis around tumour and provides a more accurate resection range for radical surgery. Some surgeons believed that anatomic resection was not mandatory for prolonging survival . Over‐pursuing anatomic resection without considering the function of the residual liver might lead to liver failure post‐operatively.…”
Section: Discussionmentioning
confidence: 99%
“…However, the available data remain insufficient to prove the prognostic advantage of AR because of substantial heterogeneity; the clinicopathologic features of patients who underwent AR or NAR are quite different among previous studies. To overcome the issue of selection bias, several case-controlled studies using PSM have recently been reported [30][31][32][33]. Cucchetti et al [30] reported favorable outcomes of AR in PS-matched populations in terms of recurrence-free survival and OS.…”
Section: Discussionmentioning
confidence: 99%
“…3 Overall survival in selected subgroup. AR anatomic resection, CI confidence interval, HBV hepatitis B virus, HCV hepatitis C virus, ICGR15 indocyanine green retention rate at 15 min, NAR non-anatomic resection, NBNC negative for hepatitis B surface antigen and hepatitis C antibody Okamura et al [32] and Marubashi et al [33] found no prognostic advantage of AR. Although these studies were performed in an attempt to minimize selection bias and imbalances in baseline characteristics by using PSM, major issues may lie in the lack of quality control of surgery and insufficient analysis of oncologic features.…”
Section: Discussionmentioning
confidence: 99%